The therapeutic process and care problems of a patient with advanced vulvar cancer - Sobala, Amelia J.; Szablewska, Anna W. (Nursing Problems / Problemy Pielęgniarstwa, 2024)
The study analysed the case of a 74-year-old woman with a diagnosis of FIGO IVA vulvar carcinoma. The patient was also suffering from other diseases such as type 2 diabetes, hypertension, obesity, and permanent atrial fibrillation. Among the patient’s most significant nursing problems, self-care deficit, impaired mobility, impaired ability to perform hygiene and self-toileting, and lack of knowledge about disease were singled out. The aim of the work is to present knowledge and explain the subject of the therapeutic process and nursing problems of a patient with advanced vulvar cancer based on an individual case study. ICNP® reference terminology was used to develop care plans. The midwife’s care of a patient with advanced vulvar cancer requires special consideration of education, health promotion, and self-management activities, assisting with hygiene activities, and providing psychological support. The overarching goal in the patient’s care is to strive for the highest possible degree of self-care.